2017
DOI: 10.1093/jrr/rrx075
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the non-thermal effects of exposing cells to 70–300 GHz irradiation using a widely tunable source

Abstract: This study investigated the effects of millimeter wave (MMW) irradiation with a wide range of frequencies on the proliferation and activity of normal human skin fibroblast (NB1RBG) and human glioblastoma (A172) cells. Very few studies have focused on low-power, long-term irradiation of cells with a widely tunable source. Our research examined non-thermal effects on cells exposed to radiation at low power with tunable frequencies from 70 GHz to 300 GHz. A widely tunable MMW source was set within a cell culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…Different aspects were studied in the in vitro studies [18,28,39,50,64,72,83,89,94,106], where nerve cell function was investigated in three studies. Two studies used nerve cells from the snail Lymnea that were exposed at 75 GHz for a few minutes at very high SAR levels (up to 4200 W/kg, power density was not reported) [28,39].…”
Section: Resultsmentioning
confidence: 99%
“…Different aspects were studied in the in vitro studies [18,28,39,50,64,72,83,89,94,106], where nerve cell function was investigated in three studies. Two studies used nerve cells from the snail Lymnea that were exposed at 75 GHz for a few minutes at very high SAR levels (up to 4200 W/kg, power density was not reported) [28,39].…”
Section: Resultsmentioning
confidence: 99%
“…The same group observed no effect of 60.4-GHz exposure on the keratinocyte transcriptome [8], although they did see a slight alteration in the transcriptome following co-exposure to millimeter waves and 2-deoxyglucose. Yaekashiwa et al reported no non-thermal effects following exposure of human skin fibroblast and glioblastoma cells to 70–300 GHz using a tunable system [25]. In summary, although several studies have examined the biological effects of millimeter-wave exposure, no study has yet obtained positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Возможно, это связано с используемыми для оценки эффектов методами. Так, методы оценки пролиферации, миграции, функциональной активности [80,82] являются менее чувствительными, чем методы молекулярной биологии, позволяющие определять как повреждения ДНК клетки, так и анализировать экспрессию определённых генов и синтез соответствующих белков [78,79,[83][84][85][86][87]. В то же время в большинстве работ, в которых наблюдалось влияние ТГц излучения, интенсивность источников значительно превышала безопасный уровень.…”
Section: влияние тгц излучения на клетки кожиunclassified